SANDWICH THEOREMS FOR ANALYTIC FUNCTIONS DEFINED BY CERTAIN NEW OPERATORS - Swamy, SR (Journal of Global Research in Mathematical Archives(JGRMA), 2013)
Abstract: In this paper we obtain some subordination and superordination results involving certain new generalized operators for certain subclasses of analytic functions in the open unit disk. Our results improve previously known results.